Study on Damage Model and Damage Evolution Characteristics of Backfill with Prefabricated Fracture under Seepage-Stress Coupling - Jifeng Hou; Zhongping Guo; Weizhen Liu; Hengze Yang; WenWu Xie (Advances in Materials Science and Engineering)
Aiming at the backfill with prefabricated fracture under seepage-stress coupling, the concepts of fracture macrodamage, loaded mesodamage, seepage mesodamage, and total damage of backfill were proposed. Based on the macroscopic statistical damage model, the coupling effect of seepage, stress, and initial fracture was considered comprehensively and the damage model of backfill with prefabricated fracture under seepage-stress coupling was established. The mechanical properties of backfill with prefabricated fracture under different seepage water pressures and confining pressures were tested and the rationality of the model was verified. The research shows that the mechanical properties of backfill with prefabricated fracture under the seepage-stress coupling are determined by the seepage water pressure, the load, the initial fracture, and the coupling effect. Fracture and seepage have significant effects on the damage of the backfill. When the seepage water pressure is low, the fracture damage dominates; however, when the seepage water pressure is high, the seepage damage dominates; the total damage under the coupling action is more serious than the single factor. The development laws of the total damage evolution curves under different seepage water pressures and confining pressures are basically the same, and they show the S-shaped distribution law with the increase of the axial strain. With the increase of confining pressure, the damage effect of fracture and seepage on the backfill is weakened, indicating that the confining pressure has a certain inhibitory effect on the damage evolution of the backfill. The research results can provide a theoretical basis for the study of the stability of backfill with geological defects such as joints and fractures in deep high-stress and high-seepage water pressure coal mines.